2020
DOI: 10.1093/cdn/nzaa045_092
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 21 Signaling Activation by Selected Bioactive Compounds from Cocoa Shell Modulated Metabolism and Mitochondrial Function in Hepatocytes

Abstract: Objectives To evaluate the effect of selected bioactive compounds from cocoa shell and its aqueous extract on the activation of fibroblast growth factor 21 (FGF21) signaling in hepatocytes and the resulting modulation of lipid and glucose metabolism, oxidative stress, and mitochondrial function. Methods The bioactive compounds from cocoa shells were extracted using water and characterized by UPLC-MS/MS. An in vitro model of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Some authors suggested that oxidative stress and mitochondrial dysfunction could be critical factors during NAFLD progression [19]. Previous studies in our group proved the effects of cocoa shell phytochemicals on protecting mitochondrial function and regulating metabolism in hepatocytes [20]. The results obtained suggest the potential role of the cocoa shell in preventing this disease.…”
Section: Discussionmentioning
confidence: 52%
“…Some authors suggested that oxidative stress and mitochondrial dysfunction could be critical factors during NAFLD progression [19]. Previous studies in our group proved the effects of cocoa shell phytochemicals on protecting mitochondrial function and regulating metabolism in hepatocytes [20]. The results obtained suggest the potential role of the cocoa shell in preventing this disease.…”
Section: Discussionmentioning
confidence: 52%
“…Mitochondrial dysfunction contributes to NAFLD's pathogenesis since it affects hepatic lipid homeostasis and promotes ROS production, lipid peroxidation, cytokine release, and cell death [16]. Previous studies demonstrated the potential effects of cocoa phytochemicals on hepatic metabolism via activation of the FGF21 signaling cascade [17], which could be associated with NAFLD prevention. Cell metabolic signaling regulation leads to a more functional phenotype in HepG2 cells than palmitic acid treated control.…”
Section: Discussionmentioning
confidence: 99%
“…De novo lipogenesis is elevated during NAFLD, and represents an important source of hepatic and circulating lipids, therefore, a decrease in this activity could lead to a decrease in their levels [24,25].Previous studies have shown that CPE and CSE could have antioxidant effects on HepG2 cell lines, probably due to their phytochemical content. Furthermore, these CSE components have been shown to protect mitochondrial function, closely related to markers associated with metabolic syndrome [11,12,26,27]. Both by-products may be recommended as therapeutic or preventive NAFLD treatments.…”
Section: Cocoa Shell and Coffee Pulpmentioning
confidence: 99%
“…The CS and the CP have been declared safe ingredients, and their characteristics and composition make them a potential source of nutrients and beneficial compounds [5,10]. Previous studies have established a relationship between phytochemicals from both the CS and the CP and the regulation of biomarkers of metabolic syndrome [3,7,11,12]. Recent research proposes that the digestion process positively influences the hypolipidemic properties of both by-products [13,14].…”
Section: Introductionmentioning
confidence: 99%